Effect of Ag+ reduction on the photocatalytic activity of Ag-doped TiO2. (September 2017) - Elsellami, L.; Dappozze, F.; Houas, A.; Guillard, C.
Abstract: Ag-doped TiO2 nanomaterials (Ag–TiO2 ) were prepared with different percentages (1%, 2%, and 4%) by a sol–gel method. This mixture was subsequently calcined at 600 °C. The structures of Ag–TiO2 nanomaterials were characterized by X-ray diffraction (XRD), UV–vis diffuse reflectance spectra (DRS) and transmission electron microscope (TEM). The evaluation of the photocatalytic activity was carried out using formic acid (FA) as a model of chemical pollutants in UV conditions. The results showed that the Ag-doping at different percentages played an important role in the microstructure and photocatalytic activity of the samples. The Ag-doped TiO2 sample at (1%) showed a photocatalytic activity about three times higher than that of P25 under UV light irradiation. Both the photocatalysis and the improvement of adsorption brought about more efficiency (1%) of Ag-doped TiO2 due to the reduction of Ag + . Graphical abstract: Highlights: More important efficiency 1% of Ag/TiO2 compared to undoped TiO2 and P25. Good correlation between adsorption and disappearance of formic acid for TiO2 doped by Ag. Samples turn to grey-black after photocatalysis due to the reduction of Ag + . Improvement of charge separation: h + react with formic acid, electron reacts with Ag + .